Relationship between senior assistant of co-curricular leadership styles and secondary school teachers' job satisfaction - Padzil, Iskandar; Foo, Say Fooi; Basri, Ramli (Human Resource Management Academic Research Society, 2017)
This study aimed to determine the teachers' perception of their Senior Assistant of Co-curricular leadership style (consideration and initiating structure) in Kota Kinabalu secondary schools in relation to their job satisfaction levels. The finding showed that Senior Assistant of Co-curricular tend to apply consideration leadership style compared to the initiating structure leadership style based on the mean comparison of both results. The survey also revealed that the leadership style of Senior Assistant of Co-curricular is located in quadrant II in the Ohio Grid of Leadership which is high consideration leadership style and moderate initiating structure leadership style. The result found that secondary school teachers in Kota Kinabalu district have a moderate level of job satisfaction and there was a significant relationship between leadership style and job satisfaction. The correlation was positive and stood at a moderate relationship. Consideration leadership style had a higher correlation with job satisfaction compared to initiating structure leadership style. The regression findings of this study support the previous studies which stated that consideration leadership style more affected to job satisfaction compared to the initiating structure leadership style. Therefore, to improve the quality of teachers' work and their job satisfaction, it is proposed that the allocation of tasks by the school administrators or policymakers need to be more efficient and balanced to achieve optimum job satisfaction among teachers.